Evolution of Primary Liquid Products and Evidence of in Situ Structural Changes in Cellulose with Conversion during Hydrolysis in Hot-Compressed Water - Yu, Yun; Wu, Hongwei (American Chemical Society, 2010)
This study shows the dynamic evolution of the primary liquid products with conversion during the hydrolysis of both amorphous and crystalline cellulose in hot-compressed water (HCW). The results suggest that the dynamic changes in cellulose structure occur during conversion and strongly depend on reaction temperature. Results from a set of purposely designed two-step experiments further confirm at least two mechanisms which may be responsible for such structural changes. One is the selective consumption of the reactive components within the intrinsically heterogeneous cellulose at early conversions. This mechanism dominates during the hydrolysis of at low temperatures, e.g., 180−200 °C for amorphous cellulose and 230 °C for microcrystalline cellulose. The other is the combined effects of various parallel reactions during hydrolysis in HCW, including cleavage of hydrogen bonds, degradation reactions, and cross-linking reactions. Enhanced hydrogen bond cleavage increases the production of glucose oligomers. However, parallel degradation reactions and cross-linking reactions decrease the selectivity of glucose oligomers. The effect of cross-linking of cellulose in HCW appears to increase with temperature and becomes significant at 270 °C, leading to a structural condensation and hence a reduction in the specific reactivity of cellulose and the selectivity of glucose oligomers in the primary liquid products.